Promosi Tenun Khas Bima Sebagai Penguatan Identitas Kota Bima Melalui Kegiatan Lombok Essay Competition - Adinda Riska Saputri; Muhammad Afrizanudin; Fajrin Hardinandar (UNIB Press, 2024)
This community service activity aims to promote and strengthen the identity of Bima City through the development of typical Bima weaving. The method is to take part in the Lombok Essay Competition Event. The activity began with cultural and economic observations in Bima City, followed by assistance in the preparation of scientific work on Bima typical weaving which was presented at the event on March 9-12 2024. The results showed that the Bima typical weaving industry provided a significant multiplier effect on other industries in Bima City. Analysis of the Input-Output derivation table shows an increase in final demand of 1.4 billion rupiah in the Bima typical weaving industry. In conclusion, this activity is able to promote Bima's typical weaving as the identity of Bima City and provide a positive economic impact, as well as having the potential to support local development and community empowerment.